Extending Object-Oriented Programming with Roles for Open Multi-Agent Systems and Its Application to ATIS - Lee, J.; Shin-Jie Lee; Chia-Ling Wu; Whan-Yo Deng (2006 IEEE International Conference on Systems, Man and Cybernetics, 2006)
The notion of organizations is getting increasing attentions for building open multi-agent systems by mimicking the collaboration of human beings for achieving the organization objectives. However, there is little support in the existing approaches to dealing with the issues of dynamic role binding towards building an agent organization in which roles and agents are designed by different designers. The main challenge is how to determine that an agent is capable of assuming a role and to build the relation between the role and the agent. As an attempt towards the investigation of the relationship between agents and roles, we propose an approach, called AgentJ a Java-based agent platform, to dealing with the issues by extending object-oriented programming with the following main features: (1) a role specification and a role matching mechanism are devised to determine whether an incoming agent is capable of assuming a role; and (2) the binding relation between agent and role is established through a role binding mechanism.